Instruktionen und andere normative Quellen zur Herrschaftsverwaltung auf den Liechtensteinischen Herrschaften Feldsberg und Wilfersdorf in Niederösterreich (1600-1815) - Hipfinger, Anita (Böhlau, 2016)
This edition collects instructions, police ordinances, decrees and related normative sources concerning the economic activities of landlords and subjects of the estates Feldsberg (today Valtice in the Czech Republic) and Wilfersdorf in the north-eastern corner of Lower Austria from the end of the sixteenth century up to 1815. All this sources illustrate the social, cultural and economic microcosm created and imagined by the authorities and show how the landlords tried to dominate and control their subjects with the help of their administrative apparatus and through regulations.